An S-type inclusion set for C-eigenvalues of a piezoelectric-type tensor. (November 2021) - He, Jun; Liu, Yanmin; Xu, Guangjun
Abstract: C-eigenvalues of piezoelectric-type tensors play the key role in Piezoelectric effect and converse Piezoelectric effect, and the largest C-eigenvalue determines the highest piezoelectric coupling constant. In this paper, an S -type inclusion set for C-eigenvalues of a piezoelectric-type tensor is given by breaking N = { 1, 2, …, n } into disjoint subsets S and its complement, which is proved always better than the existed results. Finally, numerical experiments are reported to show the efficiency of the proposed new S -type inclusion set.